Climatic Signals on Growth Ring Variation in Salix herbacea: Comparing Two Contrasting Sites in Iceland - Mohit Phulara; Magdalena Opała-Owczarek; Piotr Owczarek (Atmosphere, 2022)
Salix herbacea, being such an adaptive species, has never been studied for its climatic response. The main purpose of this study is to examine the dendrochronological potential of S. herbacea. Furthermore, it aims to identify the main environmental factors that are influencing its growth. We selected two sampling sites that are different in terms of morphology and climate. Overall, 40 samples of dwarf willow were collected from two research sites and were analyzed by following the standard dendrochronological methods. The ring width chronology of the dwarf willow from the Afrétt site spans 1953–2017, i.e., 64 years. The correlations between air temperature and the ring width of dwarf willow indicate that this species responds positively to spring and summer temperatures for the Myrdal site. For the Afrétt site, this species responds positively to winter and summer precipitation. These effects may be related to tundra browning, a process that has appeared since the beginning of the 21st century. Our work is the first attempt to create a growth ring chronology of S. herbacea and to investigate its climate sensitivity. Despite the differences in local climate in both sites, this species shows its potentiality and a direct imprint of recent environmental changes in its ring width growth pattern.